Cytotoxic cell populations in normal and alloimmunized pregnant mice. - Smith, G (1984)
Cytotoxic cell activity directed against paternal alloantigens was investigated in primiparous C57BL/10 and CBA/Ca mice using a microcytotoxicity assay. Most allogeneically or syngeneically mated females lacked effector cells in their spleens or paraaortic lymph nodes both during pregnancy and immediately postpartum. However, spleen, cells from 33% of C57BL/10 females mated to CBA/Ca males exhibited low levels of paternal target cell killing (P less than 0.05-0.01). Alloimmunization of virgin mice prior to mating resulted in only allogeneically mated females producing cytotoxic cells and alloantibody. These responses were not detectable during pregnancy but appeared immediately postpartum. The ability of pregnancy to induce memory cell formation was tested by allowing females one successful pregnancy before challenging them postpartum with allogeneic spleen cells. Kinetic studies of cytotoxic cell production showed that C57BL/10 females that had borne (C57BL/10 X CBA/Ca)F1 litters responded earlier than their syngeneically mated sisters giving a peak response at 4 days compared to 7 days after immunization. This indicates that a single allogeneic pregnancy can prime the mother against paternal alloantigens suggesting that the conceptus is weakly immunogenic.